Testing the Dielectric Permittivity Value of Three Layer Medical Mask Cloth Material with Arduino Uno Microcontroller Instrumentation System Based on Parallel Plate Capacitors - Firjatullah Akbar Putra Budiman; Elnino Profetika Zarathrustra; Agus Widayoko; Frengki Prabowo Saputro Wijayanto (Jurnal Integrasi Sains dan Quran, 2023)
The outbreak of the Covid-19 virus has caused a buildup of mask waste, especially medical masks. The use of medical mask waste as a dielectric material in capacitors can be an alternative solution to reduce the amount of mask waste. The purpose of this study was to find out the procedure for testing the dielectric permittivity value of mask cloth materials and find out the value resulting from the test. This study used parallel plates with a size of 30 x 40 cm with a thickness of 0.1 mm as capacitor electrodes. The use of the Arduino Uno microcontroller device in this study functions as a reader of the capacitance values ​​on parallel plate capacitors. The resulting capacitance value will be processed to determine the permittivity value of the dielectric material using the applicable formula or formula. This study uses two principles of capacitor stages, namely charging and discharging. The test was carried out by testing the value of each layer of the mask with three repetitions. The results showed that there were differences in the dielectric permittivity values ​​for each layer of the mask cloth. The dielectric permittivity value of the outer layer which is made from a hydrophobic non-woven layer is 1.681667, the middle layer is made from a melt blown filter of 1.860667, while the inner layer which is made from a soft absorbent non-woven layer has a permittivity value of 0. 9395. It can be concluded that the highest dielectric permittivity value is owned by the middle layer while the lowest dielectric permittivity value is owned by the inner layer. The results of this study can be used as a reference for the permittivity values ​​of materials for further research development.